Photonic nanojet-regulated soft microalga-robot with controllable deformation and navigation capability - Jianyun Xiong; Ziyi He; Guoshuai Zhu; Xing Li; Yang Shi; Ting Pan; Shuhan Zhong; He Wang; Zihao Su; Liliang Ye; Baojun Li; Hongbao Xin (PhotoniX)
Abstract Micro/nanorobots have shown great potential to execute different tasks in microenvironments due to their small size, high controllability and environmental adaptability. However, it is still challenging to precisely control the deformation and navigation of soft micro/nanorobots to better adapt to unstructured and complex surroundings. Here, we report a photonic nanojet (PNJ)-regulated soft microalga robot (saBOT) based on Euglena gracilis with controlled deformation and precise navigation capability. The deformability of the saBOT was precisely controlled by the highly focused light energy from a microlens-based PNJ bound to a tapered optical fiber probe (TFP), which can precisely stimulate the channelrhodopsin-2 (ChR2) in the photoreceptor of the microalga. This saBOT can be further precisely navigated toward different positions in complex and unstructured microenvironments by combining the deformability with the phototaxis ability of the microalga via the flexible manipulation of TFP. Notably, due to the ability of controllable deformation and precision navigation, the saBOT can travel across cell clusters for precision drug delivery toward a target cell. This PNJ-regulated saBOT holds great promise in executing different biomedical tasks in complex and unstructured microenvironments that cannot be reached by conventional tools and rigid microrobots.